Rare Combinations of Late Complications of Acute Pancreatitis and Other Diseases - D. M. Bidiuk; A. I. Furtak; A. M. Mykush (Galician Medical Journal, 2016)
Acute pancreatitis is a severe surgical disease which can be accompanied by gastrointestinal bleeding and bleeding from pancreatic pseudocysts, bowel obstruction, and perforations of peptic ulcers. The cases in which the aforementioned pathological processes were the main cause of hospitalization and lesions of the pancreas (abscess, pseudocyst) were diagnosed during treatment as a background disease are noteworthy. Clinical development and treatment of the disease were analyzed in 5 patients with the following basic pathologies: perforations of peptic ulcers (2 patients), ulcerous bleeding (1 patient), adhesive bowel obstruction (1 patient), myelofibrosis, splenomegaly (1 patient). During treatment, all the patients developed symptoms of late complications of necrotizing pancreatitis in the form of pseudocysts and abscesses which were not diagnosed before hospitalization and were characterized by an asymptomatic course. Based on the anamnesis it was revealed that all the patients were previously treated in surgical department with the diagnosis of acute pancreatitis. The possibility of an uncontrolled asymptomatic development of late complications of acute pancreatitis which further manifest themselves as background pathology and aggravate the course of other diseases was emphasized.